빅데이터 분석을 활용한 사용자 경험 평가 방법론 탐색 : 아마존 에코에 대한 온라인 리뷰 분석을 중심으로 - 황해정; 심혜린; 최준호; Hwang, Hae Jeong; Shim, Hye Rin; Choi, Junho (한국콘텐츠학회 논문지, 16(8), 2016)
This study attempted to explore and examine a new user experience (UX) research method for IoT products which are becoming widely used but lack practical user research. While user experience research has been traditionally opted for survey or observation methods, this paper utilized big data analysis method for user online reviews on an intelligent agent IoT product, Amazon's Echo. The results of topic modelling analysis extracted user experience elements such as features, conversational interaction, and updates. In addition, regression analysis showed that the topic of updates was the most influential determinant of user satisfaction. The main implication of this study is the new introduction of big data analysis method into the user experience research for the intelligent agent IoT products. 이 연구는 이미 실생활에서 사용되고 있으나 이에 대한 실증적 사용자 경험 조사가 부족한 사물인터넷 기반 제품에 대한 새로운 사용자 경험 방법론을 탐색해보고자 진행되었다. 지금까지의 사용자 경험에 대한 연구가 주로 설문이나 관찰 방법 등을 통해 이루어져 온 것과 달리 본 연구에서는 사물인터넷 기반 제품 중 지능형 에이전트인 아마존 에코(Echo)를 대상으로 사용자들의 온라인 리뷰를 분석하는 빅데이터 분석 기법을 활용하여 사용자 경험을 살펴보았다. 토픽 모델링 분석 결과, 에코의 기능, 음성 인터랙션, 지속적인 기능 개선과 관련된 사용 경험 요인들이 도출되었다. 또한 회귀분석결과 지속적인 기능 개선이 만족도에 가장 큰 영향을 미치는 것으로 나타났다. 연구의 의의는 사용자 경험을 제고할 수 있는 지능형 사물인터넷 제품 연구방법으로서 빅데이터 분석방법론 활용 가능성을 제시한 점이다.